2013
DOI: 10.5194/isprsarchives-xl-1-w1-23-2013
|View full text |Cite
|
Sign up to set email alerts
|

Precise 2-D and 3-D Ground Target Localization With Terrasar-X

Abstract: ABSTRACT:Previous studies have demonstrated the unprecedented absolute pixel localization accuracy of the German SAR (Synthetic Aperture Radar) satellites TerraSAR-X and TanDEM-X. Now, using global navigation satellite system data to locally correct for atmospheric delay, range accuracies of 1 cm are demonstrated to be attainable. Using globally available tropospheric and ionospheric delay information such accuracies can even be approached world-wide. When such accurate estimates are available for two or more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Moreover, the substantially improved localization accuracy renders new SAR applications possible, e.g. in [20] we discussed the applicability of stereo SAR.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the substantially improved localization accuracy renders new SAR applications possible, e.g. in [20] we discussed the applicability of stereo SAR.…”
Section: Discussionmentioning
confidence: 99%
“…Some improvements with respect to these issues can be expected in the near future as the monitoring system is currently being overhauled to be able to be used with the Sentine-1 constellation characterized by longer C-band wavelength and a short revisiting time of six days [65]. A possible complementary strategy to correctly detect these displacements could certainly be the so-called Imaging Geodesy (IG), exploiting the amplitude instead of (or jointly with) phase of the SAR data, as more powerful and accurate as higher resolution imagery is used [66][67][68][69][70][71].…”
Section: Discussionmentioning
confidence: 99%
“…The first results on 3D localization of CRs by means of stereo SAR was reported in [99]. Although 3D positioning using multi-aspect TerraSAR-X images had been previously demonstrated in [100][101][102], the results in [99] were unique in the sense that the stereo processing was carried out on thoroughly calibrated range and azimuth timings. Gisinger et al demonstrated the applicability of the geodetic stereo SAR method not only on CRs but on opportunistic non-ideal scatterers such as PS in an urban area [82].…”
Section: Overview Of Advancesmentioning
confidence: 99%